The relationship between the biotype of Klebsiella species and their pathogenicity. Issue 7 (July 1973) - Fallon, R. J.
Abstract : Using the biochemical scheme of Cowan, Steel, Shaw, and Duguid (1960) 209 strains of the genus Klebsiella isolated from sputum were classified and their relationship to disease in the patients from whom they were isolated was examined. K. aerogenes predominated and was seldom of proven pathogenicity. K. ozaenae was the next most common species isolated and was of pathological significance in 38% of cases. K. edwardsii var edwardsii, K. edwardsii var atlantae, and K. pneumoniae were less commonly isolated but were more frequently associated with severe disease than K. aerogenes and K. ozaenae.